“Війна” як мотив радянської ідеології в 1920 – 1930-х роках - Михайлик, Артур Олександрович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The purpose of the article is to study the meaning of the “war” motive in the ideological doctrine of Soviet Ukraine in the interwar period and to determine the peculiarities of its use as a propaganda narrative. The relevance of the study is due to the Russian-Ukrainian confrontation, which entered an active phase in 2014 and turned into an open military conflict on February 22, 2022. The study of the origins of Russian militarism will allow a better understanding of its causes and expand the possibilities of fighting the aggressor on the ideological front. The article is devoted to militarism as an important component of the ideology of the USSR and the spread of the political mythologeme of “war” on the territory of Soviet Ukraine in the interwar period. Based on the analysis of various sources, it is proved that the motive of “war” gained special scope from the beginning of the 1930s, when the Soviet Union began an active policy of aggression against neighboring states with the help of military force.